2015
DOI: 10.1016/j.bulcan.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity and consequences for targeted therapies

Abstract: SummaryAccording to the clonal model and Darwinian evolution, cancer cell evolves through new mutations helping it to proliferate, migrate, invade and metastasize. Recent genetic studies have clearly shown that tumors, when diagnosed, consist of a large number of mutations distributed in different cells. This heterogeneity translates in substantial genetic plasticity enabling cancer cells to adapt to any hostile environment. As targeted therapy focuses only on one pathway or protein, there will always be a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Primary tumor heterogeneity is a well-recognized challenge to personalized medicine [ 20 22 ]. Previous studies have revealed clonal heterogeneity of KRAS mutations within primary mCRC [ 23 , 24 ] and regarding the concordance in mutation status between primary tumors and metastatic deposits [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor heterogeneity is a well-recognized challenge to personalized medicine [ 20 22 ]. Previous studies have revealed clonal heterogeneity of KRAS mutations within primary mCRC [ 23 , 24 ] and regarding the concordance in mutation status between primary tumors and metastatic deposits [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports address this problem [58,93,98,104,[116][117][118]. Temporal heterogeneity is also an issue to consider, with clinical implications in the clinical follow-up, determining the risk of recurrence and metastases, related to acquiring resistance to chemotherapy or targeted therapy [108,109,[119][120][121][122]. Several authors have been addressing these issues.…”
Section: Doi: 101159/000487440mentioning
confidence: 99%
“…This intratumor heterogeneity is proposed to be one of the major confounding factors of treatment causing relapse and poor clinical outcome1. Genomic instability and epigenetic modifications generate intratumor heterogeneity234567 creating distinct genetic and epigenetic subpopulations or clones5891011. A branched tumour evolutionary architecture can emerge1213 containing the plasticity to progress under harsh environmental conditions and thwart therapeutic attempts to eradicate the tumour28.…”
mentioning
confidence: 99%